A powerful method for solving the power flow problem in the ill-conditioned systems. (January 2018) - Pourbagher, Rohallah; Derakhshandeh, Sayed Yaser
Highlights: Application of NLS-CLM method to solve the ill-conditioned power systems is presented. Effectiveness of the proposed method in comparison with the famous benchmark methods. Significant reduction of the CPU time in comparison with the benchmark methods. Significant reduction of the number of iterations in comparison with the other methods. Abstract: In most cases, the power systems are well-conditioned and the power flow problem (PFP) can be solved by using the famous Newton or Newton-based methods. However, in some cases, the conditions of the power systems are ill and the above-mentioned methods are poorly converged or even diverged. This paper presents application of corrected Levenberg-Marquardt algorithm with a non-monotone line search for solving the PFP in the ill-conditioned power systems. The presented algorithm is evaluated on the case studies ranging from small to large (30-bus, 57-bus, 118-bus and 2383-bus). Simulation results show the proposed approach converges in all of the case studies. Moreover, application of the proposed method for solving the PFP in ill-conditioned power systems can significantly reduce the CPU time and number of iterations in comparison with the benchmark methods.